Islam, society, and politics in Central Asia - Jones, Pauline (Central eurasia in context series, 2017)
Introduction: Reassessing the "Islamic Revival" in Central Asia / Pauline Jones -- The social significance of Islam in post-Soviet Central Asia: the case of Kyrgyzstan / Rouslan Jalil -- Beyond piety: self-related Muslims in Uzbekistan / Svetlana Peshkova -- Radical Islam from below: The Mujaddidiya and Hizb-ut-Tahrir in the Ferghana Valley / Vera Exnerova -- Engineering Islam: Uzbek state policies of control / David Abramson and Noah Tucker -- Subversives and saints: Sufism and the state in Central Asia / Emily O'Dell -- Unregistered: gray spaces in the Soviet regulation of Islam / Eren Murat Tasar -- The ascendance of orthodoxy: nation building and religious pluralism in Central Asia / Noor O'Neill Borbieva -- Islam, religious elites, and the state in post-Civil War Tajikistan / Tim Epkenhans -- When religion resorts to violence explaining variation in religious-based mobilization in Kyrgyzstan / Alisher Khamidov -- The localization of the Transnational Tablighi Jama'at Network in Kyrgyzstan / Mukaram Toktogulova -- Transnational Islamic banks and local markets in Central Asia / Aisalkyn Botoeva -- Studying Islam abroad: pious enterprises and educational aspirations of young Tajik Muslims / Manja Stephan-Emmrich -- Central Asia as part of the Islamic core / Pauline Jones